THE DIFFICULTIES FACED BY INDONESIAN EFL LEARNERS IN PRONOUNCING "S" AND "ES" SUFFIXES IN THE SIMPLE PRESENT TENSE VERBS AND IN PLURAL FORM OF NOUNS - SAPUTRA, ANDRI; HAKIM, M. ARIF RAHMAN; SAPUTRA, EKO; RAHMA, YURIKE NADIYA (Linguists : Journal of Linguistics and Language Teaching, 2020)
The authors perceive that Indonesian EFL learners find it challenging to pronounce -s and -es suffixes properly. This position was first established during the authors’ teaching experiences in some high schools, English centre course and colleges (for students majoring in English Education) in Indonesia. The observations were confirmed not only during teaching, but throughout the authors’ own English study. It seemed difficult to adhere to the rules of suffix use in spoken language, i.e. How -s and -es suffixes should and should not be pronounced during a conversation. Generally speaking, Indonesian EFL learners do not pay much attention to pronouncing the suffixes of -s or –es, and although many English users accept such mistakes in conversation with non-native speakers, it is not, however, an error a native-speaker is likely to make. In fact, this issue could lead to misunderstanding when non-native English users have conversations with native speakers. This study aims to present comparative literature review of a number research studies related to teachers’ experiences and other EFL learners. Firstly, this study explains a presentation of existing relevant research on pronunciation is offered. This is followed by an explanation of the specific difficulties faced by Indonesian EFL learners in pronouncing -s and -es suffixes in the present tense verbs and plural form of nouns. The discussion part suggests practical ways of dealing with the difficulties in pronouncing -s and -es suffixes of present tense verbs and the plural form of nouns, and proposes several activities to this end.